Integrated treatment guided by RNA-seq–based endometrial receptivity assessment for infertility complicated by MEN1 - Huang, Xi; Fu, Jing; Zhang, Qiong; Zhao, Jing; Yao, Zhongyuan; Xia, Qiuping; Tang, Hongying; Xu, Aizhuang; He, Aihua; Liang, Shaolin; Lu, Sijia; Li, Yanping (Frontiers in Endocrinology, 2023)
Background: Preimplantation genetic testing (PGT) serves as a tool to avoid genetic disorders in patients with known genetic conditions. Yet, once a selected embryo is transferred, implantation success is attained independent of embryo quality. Using PGT alone is unable to tackle implantation failure caused by endometrial receptivity (ER) abnormalities in these patients.Methods: We validated our newly developed RNA-Seq-based endometrial receptivity assessment (rsERT) in a retrospective cohort study including 511 PGT cycles and reported experience in treating an infertile female patient complicated by MEN1.Results: Significant improvement in the clinical pregnancy rate was found in the performed personalized embryo transplantation (pET) group (CR, 69.7%; P=0.035). In the rare MEN1 case, pET was done according to the prediction of the optimal time of window of implantation (WOI) after unaffected blastocysts were obtained by PGT-M, which ultimately led to a healthy live birth. But none of the mRNA variants identified in the patient showed a strong association with the MEN1 gene.Applying the new rsERT along with PGT improved ART outcomes and brought awareness of the importance of the ER examination in MEN1 infertile female patients. MEN1-induced endocrine disorder rather than MEN1 mutation contributing to the ER abnormality.4